2022
DOI: 10.3390/jcm11020370
|View full text |Cite
|
Sign up to set email alerts
|

Are Oropharyngeal Dysphagia Screening Tests Effective in Preventing Pneumonia?

Abstract: Oropharyngeal dysphagia, a clinical condition that indicates difficulty in moving food and liquid from the oral cavity to the esophagus, has a markedly high prevalence in the elderly. The number of elderly people with oropharyngeal dysphagia is expected to increase due to the aging of the world’s population. Understanding the current situation of dysphagia screening is crucial when considering future countermeasures. We report findings from a literature review including citations on current objective dysphagia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…26 Consequently, efforts should be made to prevent aspiration pneumonia through the early detection of dysphagia and several screening tests for dysphagia have been proven to be effective in predicting pneumonia. 27 Our results show that dysphagia is related to in-hospital death, especially among patients admitted for bacterial pneumonia and chronic obstructive pulmonary disease. Other studies have shown excess mortality in patients with dysphagia associated with rehabilitation, intervertebral disc disorders, heart diseases and cancer.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…26 Consequently, efforts should be made to prevent aspiration pneumonia through the early detection of dysphagia and several screening tests for dysphagia have been proven to be effective in predicting pneumonia. 27 Our results show that dysphagia is related to in-hospital death, especially among patients admitted for bacterial pneumonia and chronic obstructive pulmonary disease. Other studies have shown excess mortality in patients with dysphagia associated with rehabilitation, intervertebral disc disorders, heart diseases and cancer.…”
Section: Discussionmentioning
confidence: 60%
“…These analyses show how, independently of the reason for admission, dysphagia is associated with aspiration pneumonia, which is a complication previously related to a worse prognosis and death, even when acquired in the community 26 . Consequently, efforts should be made to prevent aspiration pneumonia through the early detection of dysphagia and several screening tests for dysphagia have been proven to be effective in predicting pneumonia 27 …”
Section: Discussionmentioning
confidence: 97%
“…Oropharyngeal dysphagia can cause substantial life-threatening complications such as aspiration pneumonia and malnutrition that are both associated with an increased morbidity [ 4 , 6 8 ], length of hospital stay [ 9 , 10 ], and tube dependency [ 11 , 12 ]. Thus, early identification of dysphagia and its timely management are vital for the reduction of these critical postsurgical sequels both for patient’s health and healthcare system [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the occurrence of dysphagia is a gradual process, along with the deterioration of cognitive functions, especially in the dementia population [ 16 , 17 ]. Continuous monitoring or frequent dysphagia screening is essential in order to mitigate the risk of choking and aspiration [ 18 ].…”
Section: Introductionmentioning
confidence: 99%